Early detection of choroidal neovascularization facilitated with a home monitoring program in age-related macular degeneration - Chaikitmongkol V. (Lippincott Williams and Wilkins, 2015)
Copyright © by Opthalmic Communications Society, Inc. Purpose: To describe clinical and imaging findings in two eyes with new onset subtle neovascular age-related macular degeneration that was detected by the regular use of a home monitoring device based on preferential hyperacuity visual field testing. Methods: Interventional case report. Results: Case 1, an 82-year-old man with the intermediate stage of age-related macular degeneration in both eyes, had been using the ForeseeHome device for 2 years when a change in test scores prompted an examination (an alert visit) to search for choroidal neovascularization (CNV) in his right eye. He denied any vision changes, and visual acuity remained 20/20 in the right eye. Fundus examination showed large drusen without any signs of CNV. The late phase of a fluorescein angiogram showed a small juxtafoveal area of subretinal leakage which corresponded to an intraretinal cystoid abnormality on optical coherence tomography. Intravitreal ranibizumab therapy was initiated, and the patient has maintained excellent visual acuity for at least 1 year. Case 2, a 67-year-old woman, had been using the home device for 3 months when an alert notification was prompted in the left eye. On notification, she recognized that she had had a subtle change in her vision in that eye with new distortion. Visual acuity decreased to 20/32 in the left eye. Fundus examination revealed stable confluent drusen without any apparent fluid, blood, or lipid. No definite fluorescein angiogram leakage was identified among the hyperfluorescent staining of extensive drusen. However, optical coherence tomography showed a cystoid abnormality in the inner plexiform layer prompting the initiation of intravitreal ranibizumab under the assumption that the changes represented CNV. Conclusion: The home monitoring device has been proven to facilitate early detection of CNV associated with age-related macular degeneration. These two cases highlight early diagnosis of CNV heralded by the device. Visual acuity remained 20/32 or better, minimal or no fluorescein angiogram leakage was found, and subtle cystoid abnormalities appeared on optical coherence tomography.